O município e a organização da educação: caminhos e desafios da criação e implantação do sistema municipal de ensino de Ananindeua-PA - PAZ, Vanilson Oliveira (Universidade Federal do Pará, 2011)
The research investigated the institutionalization process of the Educational Municipal System of Ananindeua - Pará, considering the democratization, decentralization of the education and municipal autonomy as central categories. It objectified the analysis of its organization since the creation of the Law of the Educational Municipal System, by means of the official documents that give support to it, its characterization while municipal system and the formularization of its educational politics. The methodology used was a bibliographical research and documentary analysis. The results show that the construction of the educational municipal systems at Brazil comes if giving for the recovery of the federative pact, redefining the responsibilities of the federated beings, in a context of great changes in the educational scene; the Brazilian city assumed a basic role in this organization, starting to have the legal prerogative to constitute its proper system of education; the relation between decentralization and democratization of the taking of decisions is not direct, being defended as a chance of if giving new a meaning to the forms of management of the public instances; the transference of the administration of state schools for the local level if showed as a great bias of the decentralization; the city of Ananindeua still searchs the consolidation of its system of education and, in the scope of its normative function and mobilization, it searchs the participation of the diverse segments local society. Concludes that for the creation of the EMS of Ananindeua if it made an option politics that it demanded of that they are responsible for the municipal education to assume responsibilities for its organization; its construction tried the analysis of the local problems of the education, the definition of structures and functions of the local organisms and perception of the ends and values of the local education.